2002
DOI: 10.1007/s004040100223
|View full text |Cite
|
Sign up to set email alerts
|

Clear cells carcinoma of fallopian tubes associated with tubal endometriosis

Abstract: Our case report describes a patient with clear cell fallopian tube carcinoma (histological grade 3; stage (FIGO): III c.) associated with an endometrial cyst of the tube wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…A total of 13 studies were finally considered eligible for inclusion [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 studies were finally considered eligible for inclusion [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, four were observational, which included a total of 633 patients and mainly focused on the prevalence of tubal EM among patients with various gynecological diseases, as well as on disease-related characteristics and histopathology [ 16 , 17 , 18 , 19 ], while two studies focused on analyzing the genetic profile of patients with tubal EM [ 20 , 21 ]. The remaining seven studies were case reports [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The main patient and disease characteristics of the included observational studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about its epidemiology, biology, and prognostic characteristics because primary carcinoma of a parafallopian cyst is rare. A Medline literature search using the key words ‘fallopian tube carcinoma’‘paratubal carcinoma’‘paratubal tumour’ and ‘paratubal cancer’ was performed, and although a few cases of clear cell tubal carcinoma have been reported, 3 there was no reported case of clear cell type paratubal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[46] Torre et al have described a rare case of clear cell carcinoma of the fallopian tubes associated with tubal endometriosis. [47] Gastrointestinal tract…”
Section: Cutaneous Endometriosismentioning
confidence: 99%